Colorectal Cancer Diagnosis: Tumor Stage of Screened vs. Symptomatic Patients - Segal, Joseph; Topilow, Arthur; Parker, Glenn (Journal of Coloproctology, 2025)
Objective This study aims to evaluate the utilization of colorectal cancer (CRC) screening in Monmouth County, NJ, and to compare tumor stages between patients diagnosed through screening and those presenting with symptoms. The role of nurse navigators in enhancing screening adherence and patient care was also examined.Material and Methods A retrospective chart review was conducted on 118 patients diagnosed with CRC at Jersey Shore University Medical Center (JSUMC) between January 2020 and July 2021. Data collected included initial symptoms, hemoglobin levels, age at diagnosis, screening history, cancer stage, nurse navigator involvement, and 24-month survival.Results Among patients diagnosed by symptoms (n = 83), 40% were diagnosed with Stage IV CRC versus 14% for screened patients. Of the screened patients (n = 15), 86% were alive 24 months post-diagnosis compared to 67% of symptomatic patients. Notably, 73% of all patients had never undergone CRC screening, indicating a significant gap in adherence to recommended guidelines. Only 25% of patients were assigned a nurse navigator, suggesting limited utilization of this support.Conclusions The findings demonstrate that CRC screenings were underutilized, contributing to a higher incidence of advanced-stage diagnoses and lower survival rates among symptomatic patients. Enhancing public awareness about the importance of screening, along with expanding the role of nurse navigators, may significantly improve patient outcomes and reduce the burden of advanced colorectal cancer.
Keywords: screening; CRC; symptoms; navigators